Characterization of polyethylene and polyurethane microplastics and their adsorption behavior on Cu2+ and Fe3+ in environmental matrices - Ilaria Zanoni; Lucia Briccolani; Lara Faccani; Magda Blosi; Simona Ortelli; Matteo Crosera; Giovanna Marussi; Stefania Albonetti; Anna Luisa Costa (Environmental Sciences Europe)
Abstract As the world faces growing environmental challenges, understanding the nature of microplastics—such as Low-Density Polyethylene (LDPE) and Polyurethane (PU)—and their transformation in water-based environments is necessary for predicting and mitigating their effects. In this study, we investigated their physicochemical characteristics, presence of impurities, colloidal behavior, and sorption capacity to understand better how microplastics behave and transform in the environment, including their role in transporting heavy metals. The two types of microparticles investigated fall into distinct size ranges, approximately 70 microns for PE particles and around 5 microns for PU particles. Both samples showed a spherical morphology and an evident surface micro-roughness. The elemental and thermal analysis did not show the presence of any significant metal impurities. The zeta-potential measurements as a function of pH provided insights into the dispersion behavior of microplastics (MPs) in freshwaters, suitable for the growth of Zebrafish (Egg water) and Daphnia magna (Elendt M7 Water). Both materials showed in bidistilled water negative zeta potential (ZP) at natural pH (ZP = − 51.0 ± 4.3 mV at pH = 6.6 and ZP = − 29.5 ± 1.4 mV at pH = 5.6 for LDPE and PU, respectively), justified by the presence of surface-active charged impurities. In saline media, ZP vs. pH curves were flatter, with ZP values near 0 mV, confirming the reduced colloidal stability from higher ionic strength and double-layer compression. Finally, we assessed the metal adsorption capacity to establish the role of microplastics in the transport of heavy metals in the environment. We observed selective adsorption for Cu2⁺ ions, which was both medium-dependent (more ions adsorbed in Elendt M7) and plastic-dependent, with PU showing a stronger affinity for Cu2⁺ in MilliQ and Egg water. On the contrary, both plastics showed similar adsorption capacity for Fe3⁺ ions across all media.